Effects of Salt Stress During the Growth Period on the Yield and Grain Quality of Hybrid Rice - Ruopeng Li; Dan Zhang; Yinlin Pan; Huimin Liu; Chanjuan Tang; Xiaolin Liu; Lin Mo; Yaxi Du; Guoqiang Zhou; Yuanyi Hu (Agronomy)
Hybrid rice typically surpasses conventional rice in terms of biomass, yield, and stress resistance, whereas developing and utilizing saline–alkali-tolerant hybrid rice is crucial to obtain crop harvests from salt-affected soils. In the present study, conventional rice varieties (paternal parents), i.e., Hua-Zhan and 9311, and four hybrid varieties, i.e., Xiang-Liang-You-Hua-Zhan, Jing-Liang-You-Hua-Zhan, Guang-8-You-Hua-Zhan, and Y-Liang-You-1-Hao, denoted as V1, V2, V3, V4, V5, and V6, respectively, received an application of two salt levels, i.e., 0% and 0.3% saltwater irrigation, during 2022–2023. The results reveal that the V1 (parental parent) had the highest salt tolerance index, which was significantly greater than that of its hybrid rice varieties, i.e., V3, V4, and V5. Moreover, the salt tolerance index of V2 (paternal parent) was also greater than that of its hybrid rice (V6). The lower salt tolerance index of the hybrid varieties might be owing to the lower relative loss number of effective panicles, total number of grains per panicle, seed setting rate, and thousand-grain weight. Moreover, our study revealed that the appearance of different rice varieties was enhanced at a salt concentration of 0.3%. Among all the rice cultivars, the largest reductions in chalkiness and chalky grain rate were observed in hybrid rice V3, i.e., 81.13% and 63.49%, as well as V6, i.e., 84.03% and 87.53%, respectively. The protein and sodium contents and sodium-potassium ratio of all the rice cultivars increased significantly under salt stress; however, no significant effect on cooking or sensory quality were noticed in all rice varieties under saline conditions. Overall, salt stress negatively affected the grain yield and quality, but hybrid rice is more salt-tolerant than conventional rice, harnessing heterosis to improve the yield of saline-tolerant rice.